Kajian Pemanfaatan Ebi sebagai Flavor Enhancer Alami terhadap Palatabilitas dan Analisis Usaha Siomay Kombinasi Ayam-Udang - Anis Khairunnisa; Novita Lestari; Citra Defira; Satiti Kawuri Putri (Prodi Teknologi Hasil Pertanian Universitas Sriwijaya, 2026)
Siomay is an animal protein-based processed food product characterized by a savory taste and chewy texture, requiring flavor enhancers to improve its palatability. This study aimed to analyze the effect of shrimp powder (ebi) addition as a natural flavor enhancer on the palatability of chicken–shrimp shumai and to evaluate its business feasibility. The study employed four treatments of ebi addition: D0 (0%), D1 (3%), D2 (5%), and D3 (7%). The observed parameters included sensory attributes of taste, aroma, and texture using a hedonic test, as well as business analysis consisting of Total Cost (TC), Cost of Production (COP), selling price, profit, Break Even Point (BEP), and Benefit Cost Ratio (BCR). The results showed that the addition of ebi affected the palatability of chicken–shrimp shumai, particularly in terms of taste, aroma, and texture. Treatment D2 produced the highest panelist acceptance with the most preferred taste, aroma, and texture characteristics. The business analysis indicated that all treatments were economically feasible, as shown by BCR values greater than 1. Treatment D2 demonstrated the best economic performance with a total production cost of Rp40,240 per batch, a profit of Rp17,760 per batch, and a BCR value of 1.44. Therefore, the addition of 5% ebi was considered the most optimal formulation both sensorially and economically for chicken–shrimp shumai products.